Serum CA19.9 levels are commonly elevated in primary ovarian mucinous tumours but cannot be used to predict the histological subtype. Issue 2 (12th February 2010) - Kelly, Paul J; Archbold, Pooler; Price, John H; Cardwell, Chris; McCluggage, W Glenn
Abstract : Aims: CA19.9 is a monosialoganglioside secreted by mucinous tumours of the gastrointestinal tract, including the pancreas and biliary tree. Limited studies have shown that this tumour marker may also be elevated in primary ovarian mucinous neoplasms, but no study has assessed whether serum CA19.9 levels can be used to predict if a primary ovarian mucinous tumour is benign, borderline or malignant. The aim of this study was to correlate the serum CA19.9 level with the histological features in a large series of primary ovarian mucinous neoplasms. Methods: 144 cases of primary ovarian mucinous neoplasm (79 benign, 45 borderline and 20 malignant) were identified in which a preoperative serum CA19.9 level had been performed. The association between the serum levels and the histological subtype and a variety of other parameters was investigated. In a subset of cases, immunohistochemical staining for CA19.9 was performed on tumour blocks. Results: Serum CA19.9 levels were elevated in 27%, 38% and 40% of mucinous cystadenomas, borderline mucinous tumours and mucinous carcinomas, respectively. Markedly elevated levels of serum CA19.9 were observed in each group, with the highest serum CA19.9 measurements being noted in borderline mucinous tumours. There was no relationship between the serum CA19.9 level and whether the tumours were benign, borderline or malignant (Kruskal–Wallis test p value=0.32). A weak but statistically significant correlation was found between tumour maximum dimension and CA19.9 level (Spearman's rank correlation coefficient=0.17, p=0.04). In those cases in which CA19.9 immunohistochemistry was performed, all tumours showed positive staining for CA19.9, with 60% of these cases being associated with an elevated serum CA19.9 level. Conclusion: Preoperative CA19.9 levels cannot be used to predict whether a suspected ovarian mucinous tumour is benign, borderline or malignant. Markedly elevated serum levels (>1000 U/ml) may be found in benign mucinous neoplasms as well as in borderline and malignant tumours.